LOS PLENOS JURISDICCIONALES SUPREMOS LABORALES EN MATERIA DE RESPONSABILIDAD CIVIL: ¿VINCULANTES Y NECESARIOS? - Quispe Montesinos, Carlos Alberto (Revista de Derecho, 2020)
From the analysis of the Supreme Court’s jurisdictional plenums on civil liability regarding the failure to comply with labor obligations, we evaluate the transcendence of the rules issued in them and whether they have become binding criteria for the lower level labor justice bodies. The conclusion is that such rules do not constitute binding precedents or consolidated statements generally observed by the judicial bodies of the field. Their content, in most cases, restate legal precepts and do not address essential aspects of the matter. On occasion, they have sought to modify legislation by distorting substantive and procedural institutions. Therefore, it is required that the Supreme Court issue precedents which, based on their pertinence and argument solidity, favor the predictability of the judicial decisions of the matter.